PREDICTORS OF HYPOXIC ISCHEMIC ENCEPHALOPATHY IN NEWBORNS - V. A. Sergeeva; Yu. S. Aleksandrovich; N. S. Petrenkova (Вестник анестезиологии и реаниматологии)
Goal of the study: to study the level of markers of the system fetal inflammatory response and endothelial dysfunction in the umbilical blood of full-term newborns survived after intranatal asphyxia. Materials and methods. Group 1 included 12 full-term newborns who were born with 5 and less Apgar scores for the 1st minute, and Group 2 included 12 children with a normal course of the early neonatal period. The levels of interleukin-8 (IL-8), interleukin-10 (IL-10), C-reactive protein (CRP), soluble form of E-selectin (sE-selectin) and intercellular adhesion molecule-1 (sICAM-1) in umbilical blood were tested. Results. Mothers of newborns from Group 1 demonstrated inflammatory changes in placenta compared to Group 2 (60 and 8%, p = 0.018) as well as higher levels of CRP (961 [520; 1 096] and 43 [33; 71] ng/ml, p < 0.06), IL-8 (153 [53; 323] and 28 [22; 42] pg/ml, p = 0.001), IL-10 (12.3 [7.5; 43.5] and 2.5 [1.9; 5.0] pg/ml, p < 0.001), and sICAM-1 (40 [33; 45] and 18 [17; 21] ng/ml, p < 0.06), which correlated to the inflammatory changes in placenta (r = 0.812, p = 0.028; r = 0.534, p < 0.001; r = 0.492, p = 0.034; r = 0.688, p = 0.089 for CRP, IL-8, IL-10 and sICAM-1 respectively). It was also found that Apgar score had negative correlation with IL-8 level (r = -0.453, p = 0.04 and r = -0.565, p = 0.008 on the 1st and 5th minutes respectively); IL-10 (r = -0.711, p < 0.001 и r = -0.727, p < 0.001 on the 1st and 5th minutes respectively), and sICAM-1 (r = -0.796, p = 0.013 и r = -0.904, p = 0.002 on the 1st and 5th minutes respectively). Conclusions. The system fetal inflammatory response and endothelial dysfunction related to it may predetermine the development of hypoxic ischemic encephalopathy and reduce the efficiency of treatment interventions.